Implementasi Kurikulum Montessori di PAUD - Iftiza, Fachria; Andriono, Eko; Bahari, Yohanes; Warneri, Warneri (Peneliti.net, 2025)
This study analyzes the implementation of the Montessori curriculum in Early Childhood Education (ECE) to support the development of Generation Alpha, who live in the digital era. Using a literature review method, the research explores the application of the Montessori curriculum, its diffusion as an innovation, and the factors influencing its success. Based on Everett M. Rogers’ diffusion of innovation theory, key elements such as innovation, communication channels, time, and social systems are examined within the context of the Montessori curriculum. The findings reveal that the successful implementation of this curriculum heavily depends on the synergy within the social system, involving the community, stakeholders, and the government. Collaboration among teachers, parents, and the community enhances support for the Montessori approach, while funding and professional training provided by the government improve teaching effectiveness. Although the Montessori curriculum fosters independence, creativity, and problem-solving skills in young children, the primary challenge lies in public understanding and support for children’s freedom in learning. This study underscores the importance of continuous communication and collaboration to accelerate the diffusion of innovation and ensure the successful implementation of Montessori in ECE.